Alcohol-stress interaction: possible stress alleviating prpoerties of ethanol - Urban John Arnold D'Souzaa; Ahmad Faris Abdullah; K. Dilip Murthy; David Matanjun; Fausia Jaffer; Md Tanveer Hossain; Wendy Shoesmith (Universiti Malaysia Sabah, 2015)
Stress is an inevitable part of daily life to every individual. Stress may be eustress or distress. It depends on stress exposure and individual's perception to experience the extent to which one is vulnerable. Daily stressors are unavoidable but stress coping makes an individual to tolerate stress. Many becomes the victims of alcohol drinking for the simple belief of 'tension -reduction' by the use of alcohol. Though, initially alcohol may mask few of the stress effects, its long term effects are dangerous as it may indulge in addiction behaviour. There are inconclusive reports on the interaction of stress and alcohol. There are lacunae in literature on the stress alcohol interaction especially with reference to the multi-ethnic population of the State of Sabah. Hence the objectives of the study was, to elucidate and possible stress- alcohol relationship. Whether alcohol drinking alleviates stress? Increases stress? Alcohol drinking aggravates stress? Was there any demographic, cultural factors in drinking patterns etc., Based on the previous studies, stress inventory was designed and using the DASS21 questionnaire and on its reliability and validity tests, with a voluntary consent of participants study questionnaires were introduced. Subjects of both sex 18-45 years of age were included. Exclusion criteria were chronic drinkers and those on medications for chronic diseases. The data was analysed by Structural Equation Modelling (SPSS AMOS ver 23, 2015). Results of the study revealed that, there is an association between stress and alcohol drinking. Level of stress is a major factor that is associated with level of drinking, cause of drinking among the study group. Drinking also increased the level of stress and there is interdependency between stress - alcohol drinking - stresses. In conclusion, present study confirms that, alcohol drinking does not alleviate the stress experience; on the contrary drinking alcohol increases the stress experience. It is a vicious cycle; stress experience leads to alcohol drinking, in turn alcohol drinking further increases the stress. Family and cultural drinking is one of the factors that promote alcohol drinking.